The Meaning of the Value of Responsibility from the Perspective of Students of State Vocational School 15 Bandung: A Phenomenological Study of the Implementation of Character Strengthening Education - Nurul Fauziah, Fitri; Ruyadi, Yadi; Maftuh, Bunyamin; Ganeswara, Ganjar Muhammad; Gumelar, Abih (Dinasti Publisher, 2025)
This research stems from the urgency of strengthening character education in the 21st century, which demands integration between students' cognitive, moral, and social competencies within the context of vocational education. The value of Responsibility as one of the main dimensions of character is considered increasingly important to be studied in depth, especially for Vocational High School (SMK) students who are prepared to face the world of work based on professional ethics. This study aims to understand the meaning of the value of Responsibility from the perspective of students at SMK Negeri 15 Bandung and to trace the process of its formation in the implementation of the Character Education Strengthening Program (PPK) and the West Java Priority Program. The research approach employed is a qualitative phenomenological design, involving 50 students as participants, selected through simple random sampling. Data were collected through in-depth interviews, direct observation, and documentation studies, and validated by triangulation of sources, methods, and member checks. The results show that students interpret Responsibility as moral awareness, self-discipline, and social commitment that develop through reflective interactions with teachers, the learning environment, and the habituation of values through school programs. The value of Responsibility develops in an educational ecosystem that emphasizes role models, collaboration, and students' cognitive well-being